Effects of clinical pathways for chronic obstructive pulmonary disease (COPD) on patient, professional and systems outcomes: protocol for a systematic review. Issue 1 (December 2016) - Plishka, Christopher; Rotter, Thomas; Kinsman, Leigh; Hansia, Mohammed; Lawal, Adegboyega; Goodridge, Donna; Penz, Erika; Marciniuk, Darcy
Abstract Background Chronic obstructive pulmonary disease (COPD) is a respiratory syndrome characterized by progressive, partially reversible airway obstruction and lung hyperinflation. COPD has a substantial burden which is seen in both patient quality of life and healthcare costs. One proposed method of minimizing this burden is the implementation of clinical pathways (CPWs). CPWs aim to guide evidence-based practice and improve the interaction between health services. They bring the best available evidence to a range of healthcare professionals by adapting evidence-based clinical guidelines to a local context and detailing the essential steps in the assessment and care of patients. Methods The aim of this systematic review is to synthesize existing literature on the effects of CPWs for the treatment or management of COPD. We will screen search hits from search strategies developed for a Cochrane Effective Practice and Organisation of Care (EPOC) systematic review on the use of CPWs in primary care and a Cochrane EPOC review on the use of CPWs in hospitals. These searches were run in a range of databases. Studies will be screened independently by two reviewers. All studies identified by our search strategy will be considered regardless of study design as long as they meet the operational definition for clinical pathways developed by Kinsman et al. (BMC Medicine 8, 2010) and focus on the treatment or management of COPD. All included studies will be evaluated for risk of bias utilizing methodologies set out by the Cochrane collaboration. Data regarding patient, professional and systems outcomes will be extracted from all included studies. Data will be presented in both narrative and tabular form. Discussion The systematic review outlined in this protocol aims to identify, assess and synthesise all available evidence on the effects of CPWs regarding the treatment and management of COPD. As a result, this review will provide an evidence base for decision makers regarding the practicality, cost effectiveness, patient benefit and best practices regarding the implementation of CPWs for the care of COPD.